2022
DOI: 10.1111/acv.12800
|View full text |Cite
|
Sign up to set email alerts
|

Identifying human–brown bear conflict hotspots for prioritizing critical habitat and corridor conservation in southwestern Iran

Abstract: Multiple studies have used species distribution models to identify human-wildlife conflict drivers. An important application of these models is spatial conflict resolution by accounting for habitat suitability and corridors. We used distribution and connectivity models to identify habitats and corridors for brown bear Ursus arctos in southwestern Iran with high risk of bear damages, and evaluated the effects of landscape composition and configuration on the predicted conflict hotspots. We used 154 locations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 78 publications
(132 reference statements)
0
5
0
Order By: Relevance
“…Aside from the composition of landscape, the configuration, i.e., the spatial organization of the landscape elements, can also determine the bears' behavior, and hence HBC (Linke et al, 2005;Boudreau et al, 2022). We found that HBC are more likely to occur in fragmented forests, as found elsewhere (Bombieri et al, 2018;Khosravi et al, 2022). These fragmented forests typically contain smaller, separated habitat areas with reduced natural food availability.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Aside from the composition of landscape, the configuration, i.e., the spatial organization of the landscape elements, can also determine the bears' behavior, and hence HBC (Linke et al, 2005;Boudreau et al, 2022). We found that HBC are more likely to occur in fragmented forests, as found elsewhere (Bombieri et al, 2018;Khosravi et al, 2022). These fragmented forests typically contain smaller, separated habitat areas with reduced natural food availability.…”
Section: Discussionmentioning
confidence: 68%
“…The availability of anthropogenic food (i.e., crops, livestock, and honey) is significantly related to HBC occurrences (Merkle et al, 2013;Huang et al, 2018). Furthermore, landscape composition and configuration can determine the availability and access to resources, affecting bears' behaviors and humanbear interactions (Tee et al, 2021;Khosravi et al, 2022). As found previously, HBC is more likely to occur in landscapes characterized by a complex mosaic of forest habitat patches (Boudreau et al, 2022;Khosravi et al, 2022).…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…However, we still have little to no information on the pattern and distribution of conflict events across Türkiye and our understanding of the factors that drive or increase conflict risks remains poor. Spatial information on human-brown bear conflicts (HBCs) can help us understand the ecological and anthropogenic factors responsible for these conflicts (Broekhuis et al, 2017) and develop conservation and management strategies to reduce HBCs (Hosseini et al, 2021; Khosravi et al, 2023). Therefore, the aim of this study was to quantify the spatial and temporal trends and determine the social and ecological dynamics of HBCs in Türkiye and outline bear conservation actions that can minimize these conflicts.…”
Section: Introductionmentioning
confidence: 99%